Creep behavior of intermetallic compounds at elevated temperatures and its effect on fatigue life evaluation of Cu pillar bumps. (May 2022) - Chen, Zhiwen; Yang, Fan; Liu, Sheng; Hu, Xingwang; Liu, Changqing; Zhou, Zhaoxia; Wang, Zhengzhi; Robertson, Stuart; Liu, Li
Abstract: In electronic devices, intermetallic compound (IMC) can normally be found in solder interconnects, and it can pose significant effects on mechanical integrity of interconnects. It is widely accepted that IMC is brittle and normally assumed to be elastic in related mechanical simulations. However, in this work, temperature-dependent inelastic deformation behavior of Cu6 Sn5, a common intermetallic compound in lead-free solder joints, was identified to exist at both room temperature and high temperature up to 180 °C and therefore was systematically investigated by nanoindenation. Young's modulus and hardness of IMC generally decreased linearly with increasing temperature. Creep deformation of IMC during dwelling period in nanoindentation was confirmed and further analyzed. The maximum creep displacement was found to increase from 4.90 nm at room temperature to 186.10 nm at 180 °C. Creep stress exponent was found to decrease from 3.32 to 0.37 as temperature rose, indicating significant improvement of deformation capability. Finite element modeling with and without IMC creep shows that inelastic deformation of IMC can compensate the mismatch between adjacent solder and pad in interconnects. Without considering IMC creep, fatigue life of Cu pillar bump can be severely under estimated in modelling. Highlights: Though IMC is widely accepted as elastic, temperature dependent creep has been identified from room temperature up to 180 °C. Creep stress exponent of Cu6 Sn5 was in the range of 0.37–3.32. Inelastic deformation within solder can be significantly relieved by the creep of IMCs during thermal cycling. Neglecting this creep behavior can lead to notable underestimation of predicted fatigue life of Cu pillar bumps in 3D ICs.